2016
DOI: 10.1002/cb.1586
|View full text |Cite
|
Sign up to set email alerts
|

Facebook, self‐disclosure, and brand‐mediated intimacy: Identifying value creating behaviors

Abstract: Value creating behaviors (VCBs) have not been extensively investigated within the context of social networking sites; this study highlights the importance of self‐disclosure leading to brand‐mediated intimacy as an explanation for VCBs within brand pages of social networking sites. A netnographic approach is undertaken, and the data include naturalistic observations of four Facebook brand communities. The results introduce four new VCBs and confirm that all 14 VCBs listed in previous research are practised wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
4
5
0
Order By: Relevance
“…Although similar values have been identified in the previous literature (e.g. Al-Lozi et al , 2014; Hassan et al , 2016), they were found in SNSs environments linked to bridging social capital, while the present study is one of the first to identify these values in the MIM (WhatsApp) scenario, linked to bonding social capital. In this regard, it is interesting to note that, although the values created are similar, the context and form of value creation in these two scenarios is quite different.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although similar values have been identified in the previous literature (e.g. Al-Lozi et al , 2014; Hassan et al , 2016), they were found in SNSs environments linked to bridging social capital, while the present study is one of the first to identify these values in the MIM (WhatsApp) scenario, linked to bonding social capital. In this regard, it is interesting to note that, although the values created are similar, the context and form of value creation in these two scenarios is quite different.…”
Section: Discussionsupporting
confidence: 88%
“…With other labels and with more or less disaggregation, these values have also been identified in other studies (e.g. Yavuz and Toker, 2014; Hassan et al , 2016).…”
Section: Theoretical Frameworksupporting
confidence: 79%
“…OBCs are now positioned as key platforms for facilitating the co-creation process between brands and consumers [56,57]. In this context, OBCs have facilitated co-creation through, for instance, active debate among members or collaboration in creating and developing new products [58]. Online communities can also generate ideas for new products or changes to existing ones and become a source for brand product innovation [59].…”
Section: Consumer Willingness To Co-create With the Brandmentioning
confidence: 99%
“…As it relates to the more general SNS literature, researchers should examine whether personality and/or FOMO affect various characteristics of posts. The content of the post has been shown to have an impact on how the post is perceived by other users, such as if it is a factual disclosure (includes personal facts) or an emotional disclosure (includes feelings or opinions) (Hassan, Mydock III, Pervan, & Kortt, 2016). Emotional disclosures seem to foster a more intimate relationship with the follower, according to Reis & Shaver’s interpersonal process model of intimacy (Hassan et al., 2016; Reis & Shaver, 1988).…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%